Implementasi Program Bantuan Langsung Tunai (BLT) Di Kampung Geleo Baru Kecamatan Barong Tongkok Kabupaten Kutai Barat - Tessa; Kus Indarto (Jurnal Inovasi dan Kreativitas (JIKa), 2024)
Problems: Poverty is a global social problem. so that poverty can be interpreted as a humanitarian problem that can hinder the welfare of society. The government has made various ways and efforts to overcome the problem of poverty, one of which is through a government initiative known as the Direct Cash Assistance Program (BLT). Methodology: This study uses a qualitative approach with a descriptive method. Data collection techniques in this study were carried out by observation, interviews, and documentation. Interactive model data analysis techniques. Results/Findings: The results of this study indicate that the Implementation of the Direct Cash Assistance Program in Geleo Baru Village in the first year since the launch of the program did not run well due to the inaccuracy of the timeliness of the distribution of direct cash assistance funds, which should have been received monthly due to delays from the local government which made village administrators run the program must wait for regulations from the Regent's decree so that the provision of direct cash assistance can only be given every three months. The implementation of the implementation flow, the suitability between the program and the beneficiaries did not run well, but the suitability between the program and the implementing organization, and the suitability between community groups and organizations, both flows have run well. Paper Type: Qualitative